Ammonothermal Synthesis and Characterization of First Amidozincate Hydroxides. Issue 26 (12th June 2021) - Kunkel, Sebastian; Brinschwitz, Kai L.; Richter, Theresia M. M.; Niewa, Rainer
Abstract: The first alkali metal amidozincate hydroxides Na3 [Zn(NH2 )4 ](OH) and Na3 [Zn(NH2 )3 ](OH)2 were obtained from supercritical ammonia under ammonobasic conditions at 823 K and 250 MPa, and 623 K and 159 MPa, respectively. Crystal structures have been refined against single crystal X‐ray diffraction intensity data. Coordination environments of the cations as well as the rather open crystal structure and low density of Na3 [Zn(NH2 )4 ](OH) suggest the initial formation of a monoammoniate, prior loss of ammonia during depressurizing and recovery of the product. While Na3 [Zn(NH2 )4 ](OH) contains mutually isolated amidozincate ions next to hydroxide ions, Na3 [Zn(NH2 )3 ](OH)2 is the first amidozincate realizing a condensation of the complex anionic substructure so far. Both compounds are regarded possible intermediates in an ammonothermal zinc nitride synthesis and give insights into the action of impurities during ammonothermal processes. Raman spectroscopic measurements support the assignment of amide and hydroxide groups. Abstract : Water impurities during ammonothermal synthesis lead to formation of amidozincate hydroxides, namely Na3 [Zn(NH2 )4 ](OH) and Na3 [Zn(NH2 )3 ](OH)2, rather than alternative arrangements. Synthesis and characterization of such intermediates in nitride crystal growth give insights into the action of impurities during ammonothermal processes.